2x(3x-5)-4x=2x-7

Simple and best practice solution for 2x(3x-5)-4x=2x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x(3x-5)-4x=2x-7 equation:



2x(3x-5)-4x=2x-7
We move all terms to the left:
2x(3x-5)-4x-(2x-7)=0
We add all the numbers together, and all the variables
-4x+2x(3x-5)-(2x-7)=0
We multiply parentheses
6x^2-4x-10x-(2x-7)=0
We get rid of parentheses
6x^2-4x-10x-2x+7=0
We add all the numbers together, and all the variables
6x^2-16x+7=0
a = 6; b = -16; c = +7;
Δ = b2-4ac
Δ = -162-4·6·7
Δ = 88
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{88}=\sqrt{4*22}=\sqrt{4}*\sqrt{22}=2\sqrt{22}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-16)-2\sqrt{22}}{2*6}=\frac{16-2\sqrt{22}}{12} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-16)+2\sqrt{22}}{2*6}=\frac{16+2\sqrt{22}}{12} $

See similar equations:

| -7w-41=2(w+2) | | -4(y-3)=-7y-18 | | 2x+3-4×-28=-1-20x+60 | | -8w+27=5(w+8) | | 6x-5/6=1/6 | | 2/3l-1=37 | | 50x^2-x=0 | | 15x=720 | | -2(1/3)+y=-2 | | n+3/2-n-2/5=n+1/10-1 | | 1/5x+1/4=-3(4/5x+3) | | 4(x-6)=5x+11 | | x/2+3/4=5/4 | | 4/7-7/7x=3/7 | | -4/5+y=-2 | | -n+-n−20n−-20n=6 | | r*r-7r=0 | | 2x-3/4=13/4 | | 960(1+r)^2=1123.60 | | x=24/5 | | 4=4x^2+3x | | 3(3x+4)=-5(x-8) | | 6/5x-3/2=-2/3 | | 14j−16j−-6j−-4j−-5j=13 | | 3q-2q=17 | | 16x+18-10x+14=80 | | 6=8.3^x | | x-4/5=61/2 | | 12/24=4/x | | 60s+2=8 | | 3m+2=9m | | 12c-11c=15 |

Equations solver categories